Interviews With Patients Who Traveled From Macedonia/Kosovo, The Netherlands, and Sweden for Paid Kidney Transplantations. (December 2016) - van Balen, L. J.; Ambagtsheer, Frederike; Ivanovski, N.; Weimar, W.
Background: Patients travel worldwide for paid kidney transplants. Although transplantations abroad are not always illegal, they are commonly perceived to be illegal and unethical involving risks. Aim: We aimed to describe the motivations and experiences of patients who traveled abroad for paid kidney transplantations and to examine how these transplantations were facilitated. Methods: We interviewed 22 patients who traveled from Macedonia/Kosovo, the Netherlands, and Sweden for paid kidney transplantations between years 2000 and 2009. Results: Patients traveled because of inadequate transplant activity in their domestic countries and dialysis-related complaints. However, 6 patients underwent preemptive transplantations. Cultural factors such as patients' affinity with destination countries, feelings of being discriminated against by the health-care system, and family ties also help explain why patients travel abroad. Seven of the 22 patients went to their country of origin. They were able to organize their transplantations by arranging help from family and friends abroad who provided contacts of caregivers there and who helped cover the costs of their transplants. The costs varied from €5000 to €45 000 (US6800-US61 200). Seven patients paid the hospital, 5 paid their doctor, 4 paid a broker, and 6 paid their donors. Conclusion: Research should include interviews with brokers, transplant professionals, and other facilitators to achieve a full picture of illegally performed transplantations.